The effects of combined transcranial direct Current stimulation with physiotherapy for physical function in subjects with knee osteoarthritis: a systematic review and meta-analysis. - Lozano-Meca, José; Montilla-Herrador, Joaquina; Gacto-Sánchez, Mariano (Physiotherapy Theory & Practice, 2025)
Background: Transcranial Direct Current Stimulation (tDCS) emerges as a promising therapeutic intervention for knee osteoarthritis (KOA), yet its impact on physical function remains insufficiently explored. Objectives: To evaluate the relative effects of tDCS for physical function in patients with KOA. Methods: Pubmed, Web of Science, Scopus and Cochrane Database were explored as of August 2023 to identify studies to be included in the current systematic review and metaanalysis. Randomized controlled trials in patients with KOA comparing tDCS with placebo were included. The outcomes defined were measures of physical function (questionnaires, gait, or physical performance). The Risk of Bias tool was used to assess bias in the randomized controlled trials, whereas the PEDro scale was applied for methodological quality, and the certainty of evidence for each outcome was assessed through GRADE. Results for each outcome were synthesized using meta-analysis (random-effects model, I2-test for heterogeneity) and a subgroup analysis was performed to improve the sensitivity of the results and to explore potential moderating factors of the effect sizes. Results: Ten studies with good to excellent quality were included, analyzing a total of 628 participants. Regarding physical function, tDCS showed a favorable effect (ES: −0.58; 95%CI −0.82, −0.33; I2: 52.1%) with a low risk of bias and low to moderate certainty of evidence. The concurrent application of physiotherapy interventions and tDCS improved the effects on pain and function. Applying physiotherapy interventions, as well as adding peripheral currents, increased the effect sizes (ES: −0.95, k = 3, p =.018; ES: −0.95, k = 4 p =.001, respectively). The pattern of application of the tDCS, either daily or in alternate days, did not moderate the effect size (p =.619). Meta-regression revealed that the number of tDCS sessions did not moderate the effect size either (p =.242). Conclusion: The tDCS might be a promising therapeutic approach to enhance physical function in subjects affected with KOA. However, further systematic reviews with meta-analyses should be performed with standardized and proven-efficacy physiotherapy programs, as well as with long-term results, to ascertain whether the improvement may be sustained over time. This study provides valuable insights into optimizing tDCS interventions for enhanced outcomes in the management of KOA. Protocol available via PROSPERO [CRD42023440676].